The prevalence, types, indications, and common complications associated with gynecological hysterectomy at Lautech teaching hospital, Ogbomoso, southwest Nigeria a five-year review - O. Fijabiyi, Matthew; Aworinde, Olufemi O.; Oyedeji, Ebenezer O.; Adekunle, Adebayo D.; Adegoriola, Ojurongbe O.; Muritala, Wakeel O.; Adeniran, Muibat A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hysterectomy is a common major gynecological procedure performed on women. Methods: This study was a retrospective study including all the gynecological hysterectomies done over a 5-year period in LAUTECH Teaching Hospital between 1st January 2020 and 31st December 2024. A total of 215 case files were retrieved out of 224 procedures done. Data were collected into proforma, cleaned, and analyzed using SPSS version 25. The results were expressed in frequencies, percentages, means, and standard deviation. Results: The prevalence of the gynecological hysterectomy in Ogbomoso was 25.9%. The mean age in this study was 60.9±9 years. The most common indication for hysterectomy in this environment is symptomatic uterine fibroids. The preferred approach to the procedure was the transabdominal route, constituting 91.6%. Most of the patients (88.4%) who were offered hysterectomy had salpingo-oophorectomy. About 83.7% of patients stayed within five days in the hospital following the procedure. The mean blood loss in this study was 548±352.2. Slightly below one-fourth of the total number of patients who had hysterectomies suffered one form of complication or the other. These complications include hemorrhage (31.8%), surgical site infection (18.3%), anemia (22.7%), ureteral injury (13.6%), cuff cellulitis (9%), and bladder injury (4.6%). Most (72.6%) of the histological diagnoses were benign, and the rest were malignant in nature. The most common histological diagnosis was leiomyoma (27.9%). Conclusions: Transabdominal hysterectomy is a common gynecological procedure in Ogbomoso, with symptomatic uterine fibroids being the leading indication for gynecological hysterectomy. Efforts should be made in the acquisition of skills for minimal access approaches, such as laparoscopic hysterectomy, in order to reduce complications associated with the procedure and further reduce the hospital stay.